Proceedings Title: Proceedings of the 2012 Winter Simulation Conference (WSC) 2012
DOI: 10.1109/wsc.2012.6465030
|View full text |Cite
|
Sign up to set email alerts
|

Supply chain dynamics in the SCOR model — A simulation modeling approach

Abstract: Supply Chain Simulation (SCS) is today a well-defined branch of discrete-event simulation applications. The differences between different applications are usually small, but in the case of SCS, models tend to be larger, take longer time to build and are harder to validate. To remedy some of these issues in SCS, we propose to use the SCOR model (Supply Chain Operations Reference Model) as a tool to speed up the simulation modeling of supply chains. The SCOR model can be useful in the conceptual phase, the model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Liu (2009) The SCOR model is a popular tool for designing and simulating of supply chain processes. Persson et al (2012) combined the SCOR model and discrete-event simulation to design supply chain processes. They reported that comprehensive and well-documented SCOR metrics enable faster model building for ERP-systems.…”
Section: Supply Chain Operations Reference Model (Scor)mentioning
confidence: 99%
“…Liu (2009) The SCOR model is a popular tool for designing and simulating of supply chain processes. Persson et al (2012) combined the SCOR model and discrete-event simulation to design supply chain processes. They reported that comprehensive and well-documented SCOR metrics enable faster model building for ERP-systems.…”
Section: Supply Chain Operations Reference Model (Scor)mentioning
confidence: 99%
“…One of the topical studies dealing with the SCOR model and simulation is [6]. The authors introduce the process of SCOR template development for discrete event simulation software ARENA, as well as the application of this template for creating a model and obtaining simulation results.…”
Section: Related Researchmentioning
confidence: 99%
“…In the context, the traditional simulation approach, based on the concept of discrete-event system (DES), is adhered [7]. In [6], the authors demonstrate how the main disadvantage of the SCOR model, i.e., static nature, is overcome by the dynamics of ARENA simulation model. The authors conclude that their developed SCOR template is an effective tool for faster building of SC simulations.…”
Section: Related Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, supply chain simulation is an integral part of discrete event simulation applications [10]. [11] mentions that the SCOR model can be used to build powerful Atomic Supply Chain Modelling for Risk Management based on SCOR 585 simulation models based on discrete event simulation.…”
Section: Introductionmentioning
confidence: 99%